The Effect of Host-Plant Phylogenetic Isolation on Species Richness, Composition and Specialization of Insect Herbivores: A Comparison between Native and Exotic Hosts - Grandez-Rios, Julio Miguel (PLoS One, 2015)
Understanding the drivers of plant-insect interactions is still a key issue in terrestrial ecology. Here, we used 30 well-defined plant-herbivore assemblages to assess the effects of host plant phylogenetic isolation and origin (native vs. exotic) on the species richness, composition and specialization of the insect herbivore fauna on co-occurring plant species. We also tested for differences in such effects between assemblages composed exclusively of exophagous and endophagous herbivores. We found a consistent negative effect of the phylogenetic isolation of host plants on the richness, similarity and specialization of their insect herbivore faunas. Notably, except for Jaccard dissimilarity, the effect of phylogenetic isolation on the insect herbivore faunas did not vary between native and exotic plants. Our findings show that the phylogenetic isolation of host plants is a key factor that influences the richness, composition and specialization of their local herbivore faunas, regardless of the host plant origin.